1992
DOI: 10.1016/0266-7681(92)90015-t
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Alcohol, Hepatic Pathology and Dupuytren’s Disease

Abstract: We have looked at the incidence of Dupuytren's disease in alcoholics, those with non-alcoholic liver disease and a control population. Both alcoholic patients and those with non-alcohol related liver disease had a higher rate (28% and 22% respectively) than the controls (8%), but this did not quite reach statistical significance (p greater than 0.05). In addition we found no Dupuytren's disease in 50 Egyptian patients with bilharzia and no consistent biochemical abnormalities in 134 patients with significant D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
38
0
5

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(45 citation statements)
references
References 8 publications
2
38
0
5
Order By: Relevance
“…Our results agree with those of others [17][18][19] who also have shown an insignificant relationship between alcohol consumption and DD. Therefore it is unlikely that alcohol consumption acts as an environmental influence to increase the risk of DD in susceptible individuals, suggesting that familial clustering of DD is not associated with alcohol as a shared environmental risk factor.…”
Section: Discussionsupporting
confidence: 96%
“…Our results agree with those of others [17][18][19] who also have shown an insignificant relationship between alcohol consumption and DD. Therefore it is unlikely that alcohol consumption acts as an environmental influence to increase the risk of DD in susceptible individuals, suggesting that familial clustering of DD is not associated with alcohol as a shared environmental risk factor.…”
Section: Discussionsupporting
confidence: 96%
“…It has been concluded previously that although the prevalence of DD is greater in those with considerably high consumption of alcohol, its etiologic importance may be minimal. 10 In view of the conflicting evidence on the role of smoking and alcohol in the cause of DD in the literature, and despite our findings, it was deemed appropriate to exclude alcohol consumption and smoking as part of the DD diathesis. Nevertheless, it may be that certain individuals with heavy smoking and/or alcohol habits may be further predisposed to developing DD because of gene/environment interaction, the scope and relevance of which is currently beyond the context of this article.…”
Section: Discussionmentioning
confidence: 69%
“…Most studies have found a positive association between manual labor, previous hand injuries, and intake of either alcohol or tobacco and the risk of Dupuytren's contracture [3][4][5][6][7][8][9], but some have not [10][11][12]. The underlying mechanism behind the contribution of alcohol and smoking to the fibrosis seen in Dupuytren's disease is thought to be mediated through localized ischemia and generation of free radicals; the effect of alcohol on the liver has also been suggested as a causal factor [2,13].…”
Section: Introductionmentioning
confidence: 98%